THE ROLE AND NATURE OF EVIDENCE: FORENSIC INSIGHT - Bakhtiar, Handar Subhandi (Jurnal Yuridis, 2023)
Abstract Evidence plays a pivotal role across legal, scientific, and academic domains, serving as the linchpin in distinguishing guilt from innocence. In criminal investigations, it guides law enforcement, unraveling narratives and holding perpetrators accountable. However, with the complexity of crimes, evidence can take various forms, and the clarity of accuracy may be uncertain. This study aims to investigate the diverse types of evidence and sorting procedures crucial for proving crimes. The results of this study indicate that evidence plays a crucial role in determining guilt or innocence, especially in criminal cases. Various evidence types create a nuanced dynamic in proving cases, each with distinct characteristics influencing the proof process. Sorting evidence, whether individually or through comparison, becomes pivotal in identifying the most relevant elements for legal determinations.